Additive Manufacturing of Aluminum‐Based Metal Matrix Composites—A Review. Issue 7 (1st May 2021) - Tang, Shengyang; Ummethala, Raghunandan; Suryanarayana, Challapalli; Eckert, Jürgen; Prashanth, Konda Gokuldoss; Wang, Zhi
Abstract : Al‐based metal matrix composites (AMMCs) have found enormous applications in the aerospace, automobile, and other structural applications. Compared with the conventional processes such as casting and powder metallurgy, AMMCs processed by additive manufacturing show a significant difference between microstructure and properties. This work presents the achievements of AMMCs fabricated by additive manufacturing in recent years, which is divided into six sections. Starting with the introduction, this work focuses on different fabrication methods such as composite powders and bulk material production. This is followed by discussing the microstructure in relation to the typical reinforcements and matrices, interface, and defects, and emphasizes the advantages and disadvantages compared with the unreinforced counterparts. The fourth part summarizes the recently obtained mechanical properties and the fifth part discusses the possible strengthening mechanisms and their connection with the mechanical properties. The last part is devoted to concluding the advantages, limitation, and outlook of the additively manufactured AMMCs. This review will provide a comprehensive picture of the processing–microstructure–property‐strengthening mechanisms correlation of these composites. Abstract : Al‐based metal matrix composites (AMMCs) produced by additive manufacturing show many potential promising advantages by overcoming the problems confronted in conventional processing. This work has reviewed recent progress in these composites by focusing on the preparing methods, unique structures, outstanding mechanical properties, advantages, and limitation, providing a comprehensive picture of the processing–microstructure–property‐strengthening mechanisms correlation.